Glycerol oxidation by fluorinated and platinized Titania - Bautista, E.; Ávila-Martínez, E.G.; Natividad, R.; Murcia Mesa, Julie; Romero, R.; Cubillos, J.; Hernández, J.S.; Cardenas, O.; Hidalgo, M.C.; Navío, J.A; Baeza-Jiménez, R. (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In this work, fluorinated and platinized TiO2 was evaluated in the glycerol oxidation. Fluorination led to increase the specific surface area of titania, and platinization treatment led to obtain the highest absorption in the visible region of the electromagnetic spectrum; thus, 0.5 wt.% Pt-F-TiO2 was the best catalyst in the obtention of highest yield and selectivity to glyceraldehyde (GAL). It was also found that 2wt.% of Pt content had a detrimental effect in the glycerol conversion. Fluorination and platinum addition led to modify the reaction mechanism and selectivity.